2015
DOI: 10.3389/fcvm.2015.00017
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Human Papilloma Viruses in Atheromatous Coronary Artery Disease

Abstract: ObjectiveTo identify human papilloma viruses (HPV) in atheromatous coronary arteries.BackgroundAtheromatous arterial disease is primarily an initial inflammatory response to unknown stimuli. The crucial question is “what causes the initial inflammation in atheromatous disease?” HPV infections may be relevant as US women with vaginal, high risk for cancer, HPV infections, are at up to threefold increased risk of cardiovascular disease as compared with vaginal HPV-negative women. These studies did not include an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 24 publications
2
37
0
4
Order By: Relevance
“…13 Furthermore, recent pathologic data from Lawson et al demonstrated a >50% prevalence of oncogenic HPV infection in the atheromatous coronary plaques of donors deceased from acute myocardial infarction. 25 Taken together, these studies provide support for the underlying association of HPV with the accelerated development of atherosclerosis leading stroke and TIA following RT, as noted in this study.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…13 Furthermore, recent pathologic data from Lawson et al demonstrated a >50% prevalence of oncogenic HPV infection in the atheromatous coronary plaques of donors deceased from acute myocardial infarction. 25 Taken together, these studies provide support for the underlying association of HPV with the accelerated development of atherosclerosis leading stroke and TIA following RT, as noted in this study.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, analysis from the US National Health and Nutrition Examination Survey data set revealed a >2‐fold increased risk of cardiovascular disease, including stroke, among young women with vaginal HPV infection without known cancer 13. Furthermore, recent pathologic data from Lawson et al demonstrated a >50% prevalence of oncogenic HPV infection in the atheromatous coronary plaques of donors deceased from acute myocardial infarction 25. Taken together, these studies provide support for the underlying association of HPV with the accelerated development of atherosclerosis leading stroke and TIA following RT, as noted in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations